ROMP Synthesis of Novel Thermo-, pH, and Salt Responsive (Co)Polymers Containing the Morpholino Functional Group - van Hensbergen, J.; Ganda, S.; Roth, P.; Burford, R.; Lowe, Andrew (John Wiley & Sons, 2015)
We report the ring-opening metathesis polymerization (ROMP) synthesis of novel (co)polymers containing the multiresponsive morpholino functional group [(3aR,7aS)−2-(2-morpholinoethyl)−3a,4,7,7a-tetrahydro-1H−4,7-epoxyisoindole-1,3(2H)-dione (M1)]. All (co)polymers were prepared with the Grubbs' first generation initiator, RuCl2(PCy3)2CHPh, in CH2Cl2 or CH2Cl2/2,2,2-trifluoroethanol solvent mixtures. M1 homopolymers exhibit a pH dependent aqueous solubility being fully soluble below pH 5.0 and above pH 6.0. At these intermediate values, the polymers exhibit molecular weight (MW) independent inverse temperature dependent solubility with measured cloud points (TCP) of 86 °C at pH 5.0 and 79 °C at pH 6.0. In the case of the lowest MW homopolymer (absolute MW of 9950 g/mol), there was a clear dependence of the TCP on the homopolymer solution concentration and varied over the range 78–88 °C. The TCP could be further tuned via the preparation of novel AB statistical copolymers. Incorporation of a permanently cationic comonomer as a more hydrophilic species resulted in an increase of the TCP at low incorporations (up to 10 mol %) and the complete disappearance of any temperature dependent solubility at 20 mol %. In a complementary approach, the TCP could also be lowered by the preparation of statistical copolymers of M1 with a more hydrophobic comonomer. Finally, we note that M1 homopolymers are also responsive to Na2SO4 and could be readily salted-out of an aqueous solution salt at a [Na2SO4] of 2.0 M giving a third trigger for controlling aqueous solubility. These copolymers represent examples of new multiresponsive materials and demonstrate the effectiveness of ROMP as a synthetic tool for the preparation of new and interesting materials.